Imaging Technologies in Aviation Security - Almazroui, Sultan; Wang, William; Zhang, Guangfu (European Journal of Applied Sciences, 2015)
Imaging technologies have been an essential part of security screening especially in aviation security. Aviation security uses different kinds of scanning systems including X-rays, millimeter waves. New development has been researched in both imaging technologies in the past years all over the world. Recently microwave imaging systems for security applications has been researched in the University of Sussex with new finding in the imaging results. This paper will discuss the integration, factors and other management issues when it comes to deploy new imaging technology to serve the environment of aviation security.